Association of Serum Vitamin D Levels with Cardiovascular Risk in Patients with Osteoarthritis (University Heart Journal, 2026)
Background: Osteoarthritis (OA) is a prevalent degenerative joint disorder increasingly associated with systemic comorbidities, particularly cardiovascular disease. Vitamin D deficiency is common in OA patients and may contribute to adverse cardiovascular outcomes through metabolic and inflammatory mechanisms.Aim of the study: To evaluate the association between serum vitamin D levels and cardiovascular risk in patients with osteoarthritis.Methods: This cross-sectional study included 110 patients with clinically and radiologically confirmed OA. Serum 25(OH)D levels were categorized as deficient (